Identification of T-DNA structure and insertion site in transgenic crops using targeted capture sequencing - Magembe, E.M.; Li, H.; Taheri, A.; Zhou, S.; Ghislain, M. (Frontiers Media, 2023)
The commercialization of GE crops requires a rigorous safety assessment, which includes a precise DNA level characterization of inserted T-DNA. In the past, several strategies have been developed for identifying T-DNA insertion sites including, Southern blot and different PCR-based methods. However, these methods are often challenging to scale up for screening of dozens of transgenic events and for crops with complex genomes, like potato. Here, we report using target capture sequencing (TCS) to characterize the T-DNA structure and insertion sites of 34 transgenic events in potato. This T-DNA is an 18 kb fragment between left and right borders and carries three resistance (R) genes (RB, Rpi-blb2 and Rpi-vnt1.1 genes) that result in complete resistance to late blight disease. Using TCS, we obtained a high sequence read coverage within the T-DNA and junction regions. We identified the T-DNA breakpoints on either ends for 85% of the transgenic events. About 74% of the transgenic events had their T-DNA with 3R gene sequences intact. The flanking sequences of the T-DNA were from the potato genome for half of the transgenic events, and about a third (11) of the transgenic events have a single T-DNA insertion mapped into the potato genome, of which five events do not interrupt an existing potato gene. The TCS results were confirmed using PCR and Sanger sequencing for 6 of the best transgenic events representing 20% of the transgenic events suitable for regulatory approval. These results demonstrate the wide applicability of TCS for the precise T-DNA insertion characterization in transgenic crops.